El proceso de gobernanza de la gestión de riesgos y su aplicación en el gobierno autónomo descentralizado municipal del cantón Loja - Riofrío Toscano, Marco Fabrizio (2024)
The level of risk in a society is related to its degree of development and the ability to modify inherent risk factors. In this context, risk management involves the establishment of an efficient planning, organization, direction and control process; to reduce risks, manage adverse events and recover from those that have already occurred. Accordingly, through this research work, a qualitative and quantitative study has been carried out of the current risk management process of the Municipal Decentralized Autonomous Government of the Loja canton and the guidelines that are applied to strengthen risk management governance. Initially, through the study of historical data, the frequency and impact of dangerous events in the canton during the years 2012 – 2022 are determined; 1,056 dangerous events were verified in the period, of which forest fires, landslides and floods are the most frequent events and with the greatest damage to the community and the environment; these events have their origin in both natural and anthropogenic factors. Subsequently, through research focused on citizens and the institutions that make up the local risk management system, it is proven that the absence of regulations to guide risk management in the municipality of Loja, the lack of institutional coordination, as well as the evident lack of knowledge regarding existing regulations and little citizen participation, has limited the institutionality of a local public policy for risk management, as well as the effectiveness of prevention, response and recovery actions against emergencies and disasters carried out. by the municipality of Loja. Finally, based on the results obtained, a model is proposed to strengthen the risk management process in the Decentralized Autonomous Government of the Loja canton.